Contested Heritage Jewish Cultural Property after 1945 (Edition 1) - Lucca, Enrico (2019)
In the wake of the Nazi regime's policies, European Jewish cultural property was dispersed, dislocated, and destroyed. Books, manuscripts, and artworks were either taken by their fleeing owners and were transferred to different places worldwide, or they fell prey to systematic looting and destruction under German occupation. Until today, a significant amount of items can be found in private and public collections in Germany as well as abroad with an unclear or disputed provenance. Contested Heritage. Jewish Cultural Property after 1945 illuminates the political and cultural implications of Jewish cultural property looted and displaced during the Holocaust. The volume includes seventeen essays, accompanied by newly discovered archival material and illustrations, which address a wide range of topics: from the shifting meaning and character of the objects themselves, the so-called object biographies, their restitution processes after 1945, conflicting ideas about their appropriate location, political interests in their preservation, actors and networks involved in salvage operations, to questions of intellectual and cultural transfer processes revolving around the moving objects and their literary resonances. Thus, it offers a fascinating insight into lesser-known dimensions of the aftermath of the Holocaust and the history of Jews in postwar Europe.